Blinatumomab, a Bi-Specific Anti-CD19/CD3 BiTE® Antibody for the Treatment of Acute Lymphoblastic Leukemia: Perspectives and Current Pediatric Applications - Hoffman, Lindsey; Gore, Lia (Frontiers in Oncology, 2014)
Leukemia is the most common childhood malignancy and acute lymphoblastic leukemia (ALL) represents the largest sub-type. Despite remarkable improvements over the last 40 years, standard therapy fails in 10-20% of newly diagnosed patients. Survival for children with relapsed ALL is poor, and the development and implementation of novel therapeutic strategies in pediatric ALL are critical to further advancements. Immunotherapeutic approaches have been central to more novel ALL therapies. However, more recent innovation in antibody engineering has improved potency and efficacy, and antibody-drug conjugates (ADCs) are an especially attractive option in severely immunocompromised patients. An even more sophisticated antibody design is that of bi-specific T-cell engaging or BiTE® antibodies, which directly recruit effector T cells to augment the anti-neoplastic effect. This review focuses on blinatumomab, a bi-specific anti-CD19/CD3 antibody that has shown efficacy in adult patients with precursor B-ALL and is currently being evaluated in the pediatric setting.